Comparison of Atorvastatin Alone and its Combination with Ezetimibe among Mixed Hyperlipidemic Patients (Journal of Monno Medical College, 2024)
Background: Lowering the lipid levels remains the basis of recent medical therapy for preventing cardiovascular events. Statin treatment to attain target low-density lipoprotein cholesterol (LDL-C) levels is still associated with residual risk. Objective: To compare the efficacy of Atorvastatin and Atorvastatin combined with Ezetimibe among mixed hyperlipidemic patients. Methodology: This was a prospective interventional study among the 58 diagnosed mixed hyperlipidemic patients in the outpatient department (OPD) of the Department of Cardiology at the Sylhet MAG Osmani Medical College Hospital during February to November, 2023. Patients were divided into two groups. Group I had a combination of Atorvastatin 10mg and Ezetimibe 10mg, whereas Group II took Tab. Atorvastatin 20mg once daily at night for 12 weeks. Results: After 12 weeks of treatment, a comparison of lipid profile changes between the combination therapy group and the Atorvastatin group revealed a significant reduction (p0.05). Conclusion: The study revealed that combination therapy of Atorvastatin with Ezetimibe is more effective in reducing LDL-C, TG, and total cholesterol in patients with mixed hyperlipidemia compared to Atorvastatin alone.Journal of Monno Medical College June, 2024; 10 (1):23-29